Sequencing Therapy for Optimal Response in Mirikizumab (STORM)-study: A tertiary referral center study on patients with therapy-refractory ulcerative colitis - Alica Kubesch; Raul Lande; Anna Leutgöb; Karima Farrag; Iulia Dahmer; Katharina Stratmann-Vollrath; Antje Dienethal; Florian Alexander Michael; Kathrin Sprinzl; Stefan Zeuzem; Irina Blumenstein (PLoS ONE, 2025)
Background Optimized drug sequencing is an emerging area of interest in the treatment of ulcerative colitis (UC). Comparative real-world data on treatment response to mirikizumab in a cohort with exposure to multiple biologic agents, particularly tumor necrosis factor (TNF)-naïve versus TNF-treated patients, remain limited. This study evaluated the therapeutic response to mirikizumab treatment in a cohort of patients with UC who were refractory to biologic therapy. Methods Consecutive patients with UC treated with mirikizumab between July 01, 2023, and May 31, 2025, at a tertiary university referral center were retrospectively analyzed. The primary endpoint was 12-week clinical remission. The secondary endpoints included clinical remission and biochemical remission between weeks 24 and 50 and between weeks 60 and 80. Results This study included 52 patients. Among them, 17 (32.7%) had previous exposure to ≥3 biologic agents/small molecules. The 12-week clinical remission rate was 35 of 52 patients (67.3%). There was a significant association between the treatment duration and clinical and biochemical remission. The likelihood of achieving clinical remission was 5.583 times higher after 12 weeks of intravenous mirikizumab treatment (odds ratio [OR] = 5.583, p = 0.002). Anti-TNF pretreatment had a positive effect on biochemical remission (OR = 3.489, p = 0.021). Janus kinase inhibitor pretreatment had a negative effect on clinical remission (OR = 0.19, p = 0.019). Conclusion Mirikizumab treatment had good short- and long-term efficacy in patients with UC who previously received biologic therapy. In particular, patients with prior anti-TNF therapies had favorable biochemical remission outcomes.